1997
DOI: 10.1017/s0043174500092870
|View full text |Cite
|
Sign up to set email alerts
|

Norflurazon adsorption and dissipation in three southern soils

Abstract: Norflurazon adsorption and dissipation under field and laboratory conditions, and distribution within the soil profile were determined in three soils representative of cotton-growing regions of the southeastern U.S. Norflurazon adsorption was greater in soil from 0 to 8 cm in a Lexington silt loam (Tennessee) and a Beulah silt loam (Mississippi) than in a Dothan loamy sand (Georgia). Adsorption was directly related to organic matter. Norflurazon degradation under controlled conditions in soil from 0 to 8 cm fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Field Data. A full description of all the field and labr atory methods has been previously published (Willian et al 1997a(Willian et al , 1997b. This previously reported data indicated that ftuometuron and norfturazon concentration decreased with time and that movement into subsurface soil zones was limited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field Data. A full description of all the field and labr atory methods has been previously published (Willian et al 1997a(Willian et al , 1997b. This previously reported data indicated that ftuometuron and norfturazon concentration decreased with time and that movement into subsurface soil zones was limited.…”
Section: Methodsmentioning
confidence: 99%
“…Field experiments were conducted in 1992 and 1993 at Jackson, TN, on a Lexington silt loam (fine-siltY, mixed, thermic Typic PaleudalO, at Stoneville, MS, on a Beulah silt loam (coarse-loamy, mixed, thermic typiC Dystocrept), and at Griffin, GA, on a Dothan loamy sand (Plinthic Paleudalf) using a randomized complete block design with four replications (Willian et at 1997a(Willian et at , 1997b. Plots from which the soil samples were collected were four rows wide, with rows spaced 102 em wide bY 9 m long.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of herbicide sorbed to soil is dependent on many interrelated factors, including organic matter content, soil texture, soil hydraulic conductivity, and antecedent soil moisture (Essington et al 1995;Hall et al 1989;Shankle et al 1998). Norflurazon adsorption in a Tennessee soil was greater at the 0-to 8-cm soil depth than at subsurface depths (Willian et al 1997). The decrease in norflurazon adsorption at subsurface soil zones was correlated to a decrease in organic matter at lower depths in the soil profile; however, the data of Willian et al (1997) showed that soil physical characteristics had no effect on norflurazon adsorption.…”
mentioning
confidence: 85%
“…Norflurazon adsorption in a Tennessee soil was greater at the 0-to 8-cm soil depth than at subsurface depths (Willian et al 1997). The decrease in norflurazon adsorption at subsurface soil zones was correlated to a decrease in organic matter at lower depths in the soil profile; however, the data of Willian et al (1997) showed that soil physical characteristics had no effect on norflurazon adsorption. Alternatively, some studies have shown that in addition to biotic factors, soil physical characteristics can influence herbicide retention (Baker et al 1978).…”
mentioning
confidence: 85%
“…In soil 50% loss occurs in 21–28 days according to soil type and method of application 4. Norflurazon retention in soil is related to the organic matter content,5 and the herbicide is subject to considerable leaching in sandy soils with low organic matter content 6. Norflurazon has been detected in groundwater monitoring studies on pesticides7, 8 and, in studies of pesticides in surface waters in Arkansas, norfluazon was one of the most commonly detected herbicides 7…”
Section: Introductionmentioning
confidence: 99%